Hubungan Kadar Pb Dalam Darah Dengan Kejadian Hipertensi Pada Pekerja Peleburan Timah Hitam di Perkampungan Industri Kecil (PIK) Kebasen Kabupaten Tegal - Setyabudi, Sus; Setiani, Onny; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2014)
Background: Exposure to lead (Pb) continuously for a long time will cause health effects such as hypertension, decreased the ability of the brain and inhibit the formation of red blood, disorder if it is not resolved soon be able to cause disruption to the body's various organ systems such as the nervous system, kidneys, gastrointestinal, reproductive system and hemoglobin levels. Pb in the form of fine particulate air measuring < 7µm, so it can beeasily inhaled through the respiratory tract and enter the blood circulation in the lung. Pb bound to erythrocyte and distrubuted to solf tissues such as bone marrow, brain, kidney and testis. Methods: Cross sectional study  on 45 subjects research at small Industry village kebasen talang District Tegal regency. Pb levels in the blood as biomaker of Pb exposure on  levels of blood pressure systolic, blood pressure dyastolic rate as a parameter for measuring the hypertention . Results: Subjects with lead concentrations exceeding the threshold 37 people with mean+ SD lead conceentration in 26.84+18.851;Respondents with higher levels of blood pressure systolic exceeded the 33 people with mean+SD blood pressure systolic 146.44+17.892. Respondents with blood pressure dyastolic level threshold of 10 people with a mean ± SD blood pressure dyastoliclevels of 85.47 ±11.151 . Conclusion: There is a relationship beetween blood lead concentrations in the blood pressure systolic level (p value = 0.006) with levels of blood pressure dyastolic (p = 0.036). Keywords: Lead exposure, Blood Pressure and Hypertention.